Social environment support to overcome loneliness among older adults: A scoping review - Riksa Wibawa Resna; Widianti Widianti; Wahyu Nofiantoro; Rachmayanti Iskandar; Dwi Meilina Ashbahna; Royani Royani; Susi Susilawati (Belitung Nursing Journal, 2022)
Background: Loneliness is a problem experienced by most older adults due to internal and external factors. This condition may lead to various physical and psychological health problems, including depression, sleep disturbances, stress, and suicidal ideation. Therefore, exploring social environment support to reduce loneliness is a necessity. Objective: This study aimed to identify various kinds of social support to overcome loneliness in older adults. Methods: A scoping review was performed on studies retrieved from Embase, CINAHL, Cochrane, PubMed, and Google Scholar from 2012 until early 2022. Data were analyzed according to Arksey and O’Malley’s scoping review guideline. Results: Ten studies were systematically selected from 2,410 articles. The analysis indicated that the social environment support, including family support (affection, attention, emotional, motivation, and financial support), friends (peer group, partnership, advice, and appreciation), neighbors (work around the house, society involvement, and emergency), and government support (healthcare facilities and community programs), contribute to loneliness in older adults. Conclusion: The social environment support from families, friends, neighbors, and government may potentially help older adults to reduce their loneliness but need further validation. The variables included in each component also need construct exploration. However, the study findings may serve as basic knowledge for nurses to provide interventions to prevent and reduce loneliness among older adults.